Dammarane-Type Triterpenoids from Twigs of Aglaia Foveolata and Their Antibacterial Activity - Hutagaol, Ricson Pemimpin; Mozef, Tjandrawati; Nurilmala, Febi; Primahana, Gian; Fajriah, Sofa; Prastya, Muhammad Eka; Hidayatullah, Sigit; Satyaningsih, Desy (Molekul, 2025)
ABSTRACT. The Aglaia species, which contains triterpenoids, is the most numerous in the Meliaceae family. Aglaia foveolata (A. foveolata) is a type of plant that has many benefits, as medicinal ingredients. The potential of this plant is inseparable from the content of various bioactive compounds. This study aims to isolate, characterize the active compound from the twigs of A. foveolata and test its activity as an antibacterial. Three dammarane-type triterpenoids were isolated from the A. foveolata twigs which is, namely dammar-24-en-3β,20-diol (1), an epimeric mixture of shoreic and eichlerianic acid (2, 3). Their chemical structures were determined based on spectroscopic data using infrared, high-resolution mass spectrometry, and including one and two-dimensional NMR techniques, as well as through data comparison of the reported compound. Compound 1 was reported for the first time to be successfully isolated from this species. All these substances were tested for the first time for their antibacterial activity against two Gram-positive bacteria Staphylococcus aureus and Bacillus subtilis and two Gram-negative bacteria Escherichia coli and Pseudomonas aeruginosa, through this study. Compound 1 was inactive, the epimeric mixture of 2 and 3 showed moderate antibacterial activity with a minimum inhibitory concentration (MIC) value ranging from 31.7 to 126.6 ppm, particularly against S. aureus with a MIC value of 31.7 ppm. Keywords: Aglaia, Elucidation, Isolation, Spectroscopy, Bacterial